Mataram City Student Perceptions in Recognizing and Using Smartphones - Rizaldi, Dedi Riyan; Fatimah, Ziadatul (Lembaga Riset Mutiara Akbar, 2022)
This research was conducted with the aim of knowing the perceptions of Mataram City students in recognizing and using smartphones to support their needs, especially those related to education. The type of research used is descriptive qualitative with a population of all high school students or the equivalent scattered in the city of Mataram. The sample used is 50 students from five schools. Research data in the form of survey results obtained through the process of distributing question forms using the help of links on Google Drive. The data obtained were then analyzed descriptively and supported by various relevant sources. Based on the research that has been done, it is found that the level of participation of Mataram City students in recognizing and using Smartphones is included in the high category with a percentage level of 100%. This indicates that Smartphones have become the most important part and are difficult to separate for students, especially in today's conditions